Identifying Higher-Education Level Skill Needs in Labor Markets: The Main Tools Usable for Turkey - (:unkn) unknown (My University, 2015)
0

There are natural mismatches in the labor market between the demand for higher-educated laborers and the supply of graduates provided by the higher education system in terms of quantity and qualifications. While there are open positions, some graduates still cannot find work. There are various findings indicating that the mismatch between qualification and skill is significantly high in Turkey. The fundamental political tools for reducing such mismatches include identifying the capacities of higher education programs based on skill needs, corporate structures ensuring the participation of relevant parties in the educational process, matching and consultancy services for jobseekers, and continuing education for the unemployed. Implementation of such policies depends on identifying in higher education which higher education-level skills are needed currently and for the future. The objective of this study is to identify the principal studies required to reveal the need for amount and qualifications of workers with higher education in Turkey. For this purpose, the subject is handled with theoretical foundations; field research data is evaluated and possible sets of studies and activities complying with the economic and social structure of Turkey are suggested by discussing alternative approaches and tools developed for the solution of the issue. A set of studies has been suggested under three categories (a) manpower forecasts, (b) skills needs researches generating micro data to enrich these forecasts, and (c) the information that comes from the participation and contributions of social parties in the educational process
Keywords: Eğitim, Eğitim Araştırmaları